Comparative study of hot corrosion behavior of bare and plasma sprayed Al2O3-40%TiO2 coated T-91, A-1 boiler steel and Superfer800H superalloy in Na2SO4-60%V2O5 salt environment. (28th May 2021) - Ansari, Mohd Shadab; Bansal, Amit; Chawla, Vikas; Aggarwal, Vivek
Abstract: In the present study, the bi-layer NiCrAlY/Al2 O3 -40%TiO2 coating was deposited on the three substrates (A-1, T-91, & Superfer800H) by utilizing a plasma spray technique. NiCrAlY was used as a bond coat for ensuring a proper mechanical anchorage of the topcoat (Al2 O3 -40%TiO2 ) on to it. The hot corrosion behavior of the coated as well as uncoated substrate was evaluated in an aggressive environment of Na2 SO4 -60%V2 O5 molten salt at 900 °C for 50 cycles (1 h of heating followed by 20 min of cooling at ambient temperature). Thermogravimetric analysis was done to establish the corrosion kinetics of the coated as well as the uncoated substrate. The surface morphology of the as-sprayed and corroded products was analyzed by using a scanning electron microscope (SEM) system, and various phases formed were analyzed by utilizing an x-ray Diffraction (XRD) apparatus. Iron oxide (Fe2 O3 ) is the principal phase formed in the tested uncoated substrate which is non-protective in nature; whereas the presence of Al, and Ti oxides along with some minor oxides of Ni, and Cr were observed in the oxide scale of the tested coated substrate, which are protective and remain stable even at harsh environment condition. The weight gain shown by the coated substrate is less as compared to the uncoated substrate, which indicates the usefulness of the coating.